Accuracy of Aneroid Versus Digital Sphygmomanometer in Community-Based Screening for Hypertension in Hubballi, Karnataka, India - A Cross-Sectional Study - Mahesh D Kurugodiyavar; Roopakala N; Kashavva B Andanigoudar (Medsci Publications, 2024)
Background: Hypertension is a significant global health issue, responsible for approximately 7.5 million deaths annually. Even a modest increase of 5 mm Hg in systolic blood pressure (BP) can elevate the risk of fatal stroke and infarction by about 25%. Hence this study aimed to assess the accuracy of aneroid and digital sphygmomanometers relative to the mercury sphygmomanometer. Methodology: This community-based cross-sectional study was conducted in the urban slums of old Hubballi among 270 participants aged 30 years and above. Participants were selected using Probability Proportion to Size from 3 wards. Blood pressures were measured with all three sphygmomanometers and Bland Altman plot analysis was done. Results: The results revealed that the mean difference in systolic blood pressure compared to mercury was -0.57 mmHg for the aneroid and -4.63 mmHg for the digital (p <0.05). For diastolic blood pressure, the mean difference was -0.39 mmHg for the aneroid and -3.43 mmHg for the digital (p <0.05). Bland-Altman analysis showed agreement limits of 66.3% for systolic and 75.2% for diastolic blood pressure with the aneroid sphygmomanometer. Conclusion: The aneroid sphygmomanometer provides more reliable BP readings compared to the digital sphygmomanometer for both systolic and diastolic measurements.